A Single-Institution Experience in the Use of Chest Radiographs for Hospitalized Children Labeled as Asthma Exacerbation - Beyyumi, Ela; Tawil, Mohamed I.; AlDhanhani, Huda; Jameel, Sara; Mouhssine, Manal; AlNuaimi, Hasa M.; Hamdoun, Osama; Alabdouli, Amnah; Alsamri, Mohammed T.; Ghatasheh, Ghassan A.; Zoubeidi, Taoufik; Souid, Abdul-Kader (Frontiers in Pediatrics, 2021)
Background: Risks of diagnostic radiation have become more notable lately, particularly in young children with chronic medical conditions. This study reports on the cumulative radiation from chest radiographs in children with asthma. Its main purpose was to review our current practice and suggest minimizing the use of chest radiographs. Methods: The study was retrospective and conducted at a pediatric tertiary center. Eligibility criteria included children 2-15 y, admitted between January 2017 and December 2018 for asthma management. Results: Of the 643 children admitted as ‘asthma exacerbation’, 243 (40% females; age [mean±SD] 5.4±3.3 y) met the study criteria for inclusion. Ninety-two (38%) children had a temperature of 38.8±0.7oC on the day of admission. Antibiotics were prescribed for 148 (61%) children, mainly for presumed pneumonia. Chest radiographs were requested for 214 (88%) children, mainly on the day of admission. Only 38 (18%) chest radiographs showed focal/multifocal pneumonia justifying antibiotic use. Significant predictors for requesting chest radiographs were antibiotic use for presumed pneumonia, lower oxygen saturation at presentation, and a requested blood culture. The rate of chest radiographs per year was negatively related to the child’s age; the younger the child the higher the rate (model coefficient -0.259, P<0.001). For children <5 y, the rate of chest radiographs was 1.39±1.21/y and radiation dose 0.028±0.025 mSv/y. The corresponding rates for children ≥5 y were 0.78±0.72/y and 0.008±0.007 mSv/y, respectively (P<0.001). Conclusion: Chest radiographs were commonly requested for children with asthma, especially younger children. Prospective studies are necessary to measure the impact of this practice on the children’s health.